Analisis Current Ratio, Debt to Equity Ratio, dan Return on Equity pada Perusahaan Farmasi yang Terdaftar di BEI Tahun 2018-2020 - Pindy Widiya Pratiwi; Yeni Kuntari; Iin Indarti (Jurnal Ilmiah Aset, 2022)
The pharmaceutical industry is a research-based industry. As time goes on, there is an increasing demand for producing medicinal products, medical devices in the health sector, of course, will have a positive impact on the growth of pharmaceutical companies listed on the Indonesia Stock Exchange. Funding is one of the important factors to face competition. This funding source is also called the source of own capital funding. For investors, there are three most dominant financial ratios that are used as a reference to see the condition of a company's performance, namely the liquidity ratio (Current Ratio), solvency ratio (Debt to Equity Ratio), and profitability ratio (Return on Equity). The purpose of this study was to determine and analyze the Current Ratio, Debt to Equity Ratio, and Return on Equity of pharmaceutical companies listed on the Indonesia Stock Exchange in 2018-2020. Based on the calculation of the ratio value of 4 pharmaceutical companies in 2018-2020, the average CR is 273%, which means it is categorized as good in paying short-term debt. The average DER is 1.04%, which means it is very good at paying off its short-term debt and making a profit. While the ROE is 0.18%, which means that it becomes an attraction for investors to invest in these pharmaceutical companies.